(untitled) (American Journal of Islam and Society, 2016)
The seventeenth century marks an exciting period in the life of Persian literary cultures in northern India. Established as a language of administration by Turco-Afghans in the early thirteenth century, several centuries later Persian had extended well beyond its initial administrative strongholds to become an important medium for literary and religious composition, historiography, and translation. In a literary environment that prized both literary aesthetics and fierce rivalries, the massive textual production on vastly diverse subjects, as well as the presence of literary salons, standalone bookstalls, and mushā‘irahs (poetic assemblies), cumulatively point to a lively Persian literary culture that echoed across political, religious, and socio-cultural terrains. Unfortunately, most of the scholarship on Persian in the medieval Indian context over the past decades has failed to illuminate this dynamic scene. Moreover, most studies seek to highlight Persian’s influence on India or examine India’s civilizational impact on Persian. Both paradigms assume a natural (read: Iranian) ecumene for Persian and thus do not critically consider the slippage between linguistic, ethnic, and geographic designations wh